2008
DOI: 10.1016/j.mce.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and the selective estrogen receptor modulator (SERM) protection against cell death in estrogen receptor alpha and beta expressing U2OS cells

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Transfection with either of the ERs was able to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…E2 (10 -8 ∼10 -10 M) has similar ability to stimulate the induction of collagenase-3 mRNA in UMR 106-01 cells (Partridge et al, 2000). Transfection with either ERα or ERβ causes U2OS cell sensitivity to E2 (Lima et al, 2004;Kallio et al, 2008). We previously reported that E2 (1 μM) does not positively regulate cell proliferation in MC-3T3-E1 cells (Guo et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…E2 (10 -8 ∼10 -10 M) has similar ability to stimulate the induction of collagenase-3 mRNA in UMR 106-01 cells (Partridge et al, 2000). Transfection with either ERα or ERβ causes U2OS cell sensitivity to E2 (Lima et al, 2004;Kallio et al, 2008). We previously reported that E2 (1 μM) does not positively regulate cell proliferation in MC-3T3-E1 cells (Guo et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…First, the influence of FC on ERα transcriptional activity was tested, as well as the role of the F-domain C-terminal tip therein. To rule out any influence of endogenous receptor, we made use of ERα-negative human osteosarcoma cell line U2OS, a wellannotated model system for ERα action (30). ERα-mediated estrogen response element-luciferase reporter (ERE-luc) expression was measured in U2OS cells cotransfected with ERα wild type (ERα-WT) and two C-terminal mutants: ERα-T 594 A and ERα-Δ4, a construct lacking the last four amino acids.…”
Section: Yellow) (E) Perα (Green) Interaction With 14-3-3σ (Gray) (F)mentioning
confidence: 99%
“…Although the protective effect of raloxifene on bone mass is known, less is known regarding its action mechanism. It has been suggested that raloxifene prevents osteoblast death and inhibits oxidative stress-induced endothelial cell apoptosis (16,36). These effects may operate through a receptor-independent mechanism related to the antioxidant activity of SERMs (36).…”
Section: Raloxifene Effects On Avcmentioning
confidence: 99%
“…It is a mixed estrogen receptor agonist and antagonist, which has been shown to reduce cardiovascular events in women at high risk for coronary artery disease (5). Although the mechanism of the raloxifene effect on atherosclerosis is not completely understood, it has been shown to reduce both osteoblast cell apoptosis and oxidative stress damage (16,36). However, its role in valvular calcification is still unknown.…”
mentioning
confidence: 99%